Estimating components of ICT expenditure: a model-based approach with applicability to short time-series - Cooper, R.; Madden, Gary (Taylor & Francis, 2010)
This article develops a microeconomic model-based approach to estimation of national information and communications technology expenditure that is helpful when only very short time-series are available. The model specification incorporates parameters for network effects and national e-readiness. Finally, the model allows for observed nonhomotheticity and ‘noise’ found in sample data, with the latter attributed to country-specific influences.